Combined effects of hepatocyte nuclear factor 4α and constitutive androstane receptor on stable warfarin doses. Issue 1 (January 2015) - Moon, Jung Yeon; Lee, Kyung Eun; Chang, Byung Chul; Jeong, Eurim; Jeong, Hotcherl; Gwak, Hye Sun
<x xml:space="preserve">Abstract</x> A possible association between the combination of genetic variations in hepatocyte nuclear factor 4α (HNF4α) and constitutive androstane receptor (CAR) and the stable doses of warfarin was examined in patients from the Ewha–Severance Treatment (EAST) Group of Warfarin. Around 42.5% of the overall interindividual variability in warfarin dose requirements was explained by the multivariate regression model; the vitamin K epoxide reductase complex 1 (VKORC1) genotype accounted for 29.6%, the cytochrome P450 (CYP) 2C9 genotype for 4.3%, age for 3.6%, the CYP4F2 genotype for 3.3%, and CAR/HNF4α (rs2501873/rs3212198) for 1.7%. Our results showed that the combination of CAR and HNF4α genotypes could be determinants of stable warfarin doses.